Labour market flexibility and regional unemployment rate dynamics: Spain 1980 - 1995 - Roberto Bande; Marika Karanassou (Queen Mary University of London, Department of Economics, 2006)
This paper aims to shed light in the dynamics of Spanish regional unemployment rates and determine the driving forces of their disparities. The Spanish economy has one of the highest unemployment rates in the EU and is characterised by severe regional disparities. We apply the chain reaction theory of unemployment according to which the evolution of unemployment is driven by the interplay of lagged adjustment processes and the spillover effects within the labour market system. Our model includes nationwide as well as region-specific variables, and takes into account the limited labour and firm mobility in Spain. We show that the degree of labour market flexibility differs between high and low unemployment regions, and find that investment has a major influence on the unemployment trajectory. In addition, we find that in bad times high unemployment regions are hit more severely than low unemployment regions, while in good times high unemployment regions do not benefit as much as low unemployment regions.
Keywords: R23; J64; 330; Regional disparities; Unemployment; Spillover effects; Labour market lagged adjustment processes